Sleep disturbance as a mediator of the relationship between perceived stress and demoralization in hemodialysis patients: a structural equation modeling analysis - Ye, Yansheng; Zhang, Jing; Sun, Yane; Xu, Jianqing; Xu, Qian; Song, Chengrong (Frontiers in Psychiatry, 2025)
BackgroundDemoralization describes a state of existential distress, isolation, impotence, hopelessness, helplessness, and loss of purpose and meaning in life. Demoralization is associated with suicidal thoughts, which could lead to a desire for hastened death. Perceived stress could be viewed as the sense of imbalance between the stressors experienced by an individual in daily life and his or her coping capability. Many studies have tested the relationships between perceived stress, sleep disturbance, and demoralization; however, the mechanism of sleep disturbance has not been fully evaluated.ObjectiveTo verify the relationship between perceived stress and demoralization and explore the mediating effect of sleep disturbance on the relationship between perceived stress and demoralization in hemodialysis patients.Materials and methodsA cross-sectional questionnaire survey using convenience sampling from July to August 2022, 547 hemodialysis patients from ten hospitals filled out the Perceived Stress Scale (PSS), Pittsburgh Sleep Quality Index (PSQI), Demoralization Scale (DS), and general information questionnaire. The data were analyzed using SPSS 26.0, and path analysis and structural equation modeling were used to explore the relationships among perceived stress, sleep disturbance, and demoralization.ResultsPerceived stress was significantly and positively associated with demoralization (P < 0.01) among hemodialysis patients. Sleep disturbance partially mediated the relationship between perceived stress and demoralization (B = 0.154, 95% CI: 0.102~0.213); the proportion of mediation was 43.75%.ConclusionPerceived stress affects demoralization among hemodialysis patients, and sleep disturbance is a mediator in the relationship. Perceived stress in hemodialysis patients should be measured and effectively managed to improve positive effects on demoralization. It is necessary for medical staff to consider implementing perceived stress interventions with an emphasis on construction of sleep strategies to assist hemodialysis patients improve their demoralization.